2018
DOI: 10.1101/246637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massive postglacial gene flow between European white oaks uncovered genes underlying species barriers

Abstract: Oaks are dominant forest tree species widely distributed across the Northern Hemisphere, where they constitute natural resources of economic, ecological, social and historical value. Hybridization and adaptive introgression have long been thought to be major drivers of their ecological success. Thus, the maintenance of species barriers remains a key question, given the extent of interspecific gene flow. In this study, we scanned the genomes of four European white oak species for reproductive barriers. We ident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…All of these factors may ultimately affect demographic inferences (Cutler & Jensen, 2010;Harvey, Smith, & Glenn, 2016). In such cases, Pool-seq has already proven to be an effective and accurate approach to investigate genomewide variations of terrestrial and marine high gene flow species such as oaks (Quercus spp., Leroy et al, 2018), poplar (Populus alba, Stölting et al, 2015;Populus alba, Populus tremula, Christe et al, 2016), Chinese chestnut (Castanea mollissima, LaBonte, Zhao, & Woeste, 2018), sticklebacks (Gasterosteus aculeatus, Guo, DeFaveri, & Sotelo, 2015), Atlantic herring (Clupea harengus, Guo, Li, & Merilä, 2016;Lamichhaney et al, 2012;Martinez Barrio et al, 2016), Atlantic cod (Gadus morhua, Karlsen et al, 2013), and the copepod (Tigriopus californicus, Lima & Willett, 2018). On the other hand, and pending on specific research objectives, quantifying genetic parameters where individual information is required may not always be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors may ultimately affect demographic inferences (Cutler & Jensen, 2010;Harvey, Smith, & Glenn, 2016). In such cases, Pool-seq has already proven to be an effective and accurate approach to investigate genomewide variations of terrestrial and marine high gene flow species such as oaks (Quercus spp., Leroy et al, 2018), poplar (Populus alba, Stölting et al, 2015;Populus alba, Populus tremula, Christe et al, 2016), Chinese chestnut (Castanea mollissima, LaBonte, Zhao, & Woeste, 2018), sticklebacks (Gasterosteus aculeatus, Guo, DeFaveri, & Sotelo, 2015), Atlantic herring (Clupea harengus, Guo, Li, & Merilä, 2016;Lamichhaney et al, 2012;Martinez Barrio et al, 2016), Atlantic cod (Gadus morhua, Karlsen et al, 2013), and the copepod (Tigriopus californicus, Lima & Willett, 2018). On the other hand, and pending on specific research objectives, quantifying genetic parameters where individual information is required may not always be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…These two species display subtle differences in soil preferences when present in the same forest (Timbal & Aussenac, 1996;Eaton et al, 2016), but they also have different climate responses, as suggested by their allopatric (temperature-and precipitation-dependent) distributions at the edge of their ranges. Q. robur extends farther north (up to Finland) and east (up to the Ural Mountains) (see Leroy et al, 2018), and has a higher frequency in wetter climates (Eaton et al, 2016). We suspect that the introgression of Q. robur alleles for genes involved in these differential responses may have contributed to the expansion of Q. petraea populations to higher elevations in the Pyrenees and wetter climates in Ireland.…”
Section: Petraeamentioning
confidence: 99%
“…Shortlisted among the ‘botanical horror stories’ (Rieseberg et al, 2006), the Quercus genus constitutes an ideal taxon to investigate the dynamics of lineage diversification along a wide and fluid continuum of speciation. Several efforts to illuminate oak evolutionary histories using population genomic approaches have recently emerged (Ortego et al, 2016, 2018; Leroy et al, 2017, 2018). In European white oaks for example, the best-supported scenario of divergence is consistent with a long-term pervasive effect of interspecific gene flow, with the exception of some narrow genomic regions responsible for reproductive isolation.…”
Section: State Of the Sciencementioning
confidence: 99%